Phenomenon of ignition and explosion of high-entropy alloys of systems Ti-Zr-Hf-Ni-Cu, Ti-Zr-Hf-Ni-Cu-Co under quasi-static compression - Sergiy Kotrechko; Oleksandra Zatsarna; Oleksandr Filatov; Vadim Bondarchuk; Georgiy Firstov; Vladimir Dubinko (Fracture and Structural Integrity)
The phenomenon of ignition and explosive failure of specimens from high-entropy alloys (HEAs) of systems Ti-Zr-Hf-Ni-Cu, Ti-Zr-Hf-Ni-Cu-Co at quasi-static compression tests was found. It physical model is proposed. It is exhibited that the reason for this phenomenon is the release of energy of the oxidation reaction; such reaction is initiated due to the heat released ahead of the shear crack tip at brittle fracture of the specimens under quasi-static compression. It is shown that ignition and failure by explosion are the specific features of brittle fracture for high-entropy alloys containing Ti-Zr-Hf, in general. This phenomenon is realised when certain critical levels of strength and ductility of these alloys are reached. The importance of these critical levels of strength and ductility lies in the fact that they predetermine the maximum permissible level of strength and brittleness for this class of HEAs, above which they lose their structural and functional properties, turning to the energetic alloys capable of explosive release of a significant amount of thermal energy. This specific feature of the high-entropy alloys containing Ti-Zr-Hf outlines the scope of their application and defines the boundary separating structural and functional high-entropy alloys from energetic high-entropy alloys